Observing the emergence of a quantum phase transition shell by shell - Bayha, Luca; Holten, Marvin; Klemt, Ralf; Subramanian, Keerthan; Bjerlin, Johannes; Reimann, Stephanie M.; Bruun, Georg M.; Preiss, Philipp; Jochim, Selim (Nature, 2020)
Many-body physics describes phenomena that cannot be understood by looking only at the constituents of a system. Striking examples are broken symmetry, phase transitions and collective excitations. To understand how such collective behaviour emerges as a system is gradually assembled from individual particles has been a goal in atomic, nuclear and solid-state physics for decades. Here we observe the few-body precursor of a quantum phase transition from a normal to a superfluid phase.
Gesehen am 15.12.2020